2012
DOI: 10.1016/j.prevetmed.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of baiting on feral swine behavior in the presence of culling activities

Abstract: We studied the effects of baiting on feral swine (Sus scrofa) movements and corresponding likelihood of disease spread under real and simulated culling pressure. Our objectives were to determine the proportion of feral swine that used the bait station site, and if baiting of feral swine altered areas of utilization, distances from location centroids to treatment location (control or bait station), and movement rates by survivors during culling activities. We hypothesized that the bait station would increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
(53 reference statements)
1
9
0
Order By: Relevance
“…Although this removal activity was only applied once to collared feral swine, these findings support our first removal activity results. Similarly, population-wide culling activities, including trapping, controlled shooting, drive shooting, and aerial gunning that incorporated a centralized bait station, had no effect on size of areas used by feral swine, but movement rates at bait stations were greater compared to control sites (Campbell et al 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although this removal activity was only applied once to collared feral swine, these findings support our first removal activity results. Similarly, population-wide culling activities, including trapping, controlled shooting, drive shooting, and aerial gunning that incorporated a centralized bait station, had no effect on size of areas used by feral swine, but movement rates at bait stations were greater compared to control sites (Campbell et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…There have been no research efforts devoted to understanding how multiple types of removal activities might affect feral swine behavior in North America (except, see Campbell et al 2012). Our study goals were to determine if repeated simulated removal activities altered the size or location of space-use areas and assess differences in feral swine movements before, during, and after simulated removal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Use of the landscape by wild pigs is primarily driven by the location and availability of food and water . However, previous research has shown that wild pigs will adjust their space‐use to utilize transitory anthropogenic food sources, such as bait or crops .…”
Section: Introductionmentioning
confidence: 99%
“…8 Use of the landscape by wild pigs is primarily driven by the location and availability of food and water. [9][10][11][12] However, previous research has shown that wild pigs will adjust their space-use to utilize transitory anthropogenic food sources, such as bait or crops. [10][11][12][13] Some wild pigs shift their home ranges to include these types of resources or constrict their movements around such resources demonstrating the importance of thoughtful spatial strategies when deploying bait stations to maximize bait delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the devastating history of many lethal control programmes, removal has a legitimate role in wildlife management in many countries and does contribute to coexistence between people and wildlife (Treves and NaughtonTreves 2005). As lethal wildlife management is an important approach in environmental management, and has been practised on various wildlife species in many countries, such as feral camels in Australia (Edwards et al 2008), elephants in Africa ( van Aarde, Whyte and Pimm 1999;Koenig 2007), swine in the US (Campbell et al 2012), it is critical to understand the environmental consequences of such a management approach. Carbon emissions are one part of such consequences that requires concern.…”
Section: Introductionmentioning
confidence: 99%